Study Of Problems And Disorders In Dental Clinics Architectural Design - Pasaeian, Mojhgan; Saeidi, Mohammad (The Turkish Online Journal of Design Art and Communication, 2016)
Hasty process, outlawed development and principles of architecture of dental clinics in most cities, has changed the situation in such a way that the dental clinics, special new build clinics they are new physical and aesthetic architecture have been significant problems in dental clinic cannot give material and physical needs of peoples the answer them dignity and also cannot have a sense of relaxation in a space of their spiritual needs and embrace. In this paper, by examining the validity of the staff and patients of dental clinics we explain and we will prove that the challenges of architecture and planning in the design of dental clinics in Tehran and other big cities as the model cases that compliance with them, a consideration of the dignity of patients and staff of dental clinics in mental peace be maintained as well as the proper use of science and new development.
Keywords: architecture; dentistry; clinic; design; Tehran